Effect of Aspirin on Development of ARDS in At-Risk Patients Presenting to the Emergency Department: The LIPS-A Randomized Clinical Trial - Kor, Daryl J. (JAMA, 2016)
IMPORTANCE: Management of acute respiratory distress syndrome (ARDS) remains largely supportive. Whether early intervention can prevent development of ARDS remains unclear. OBJECTIVE: To evaluate the efficacy and safety of early aspirin administration for the prevention of ARDS. DESIGN, SETTING, AND PARTICIPANTS: A multicenter, double-blind, placebo-controlled, randomized clinical trial conducted at 16 US academic hospitals. Between January 2, 2012, and November 17, 2014, 7673 patients at risk for ARDS (Lung Injury Prediction Score≥4) in the emergency department were screened and 400 were randomized. Ten patients were excluded, leaving 390 in the final modified intention-to-treat analysis cohort. INTERVENTIONS: Administration of aspirin, 325-mg loading dose followed by 81mg/d (n = 195) or placebo (n = 195) within 24 hours of emergency department presentation and continued to hospital day 7, discharge, or death. MAIN OUTCOMES AND MEASURES: The primary outcome was the development of ARDS by study day 7. Secondary measures included ventilator-free days, hospital and intensive care unit length of stay, 28-day and 1-year survival, and change in serum biomarkers associated with ARDS. A final α level of .0737 (α = .10 overall) was required for statistical significance of the primary outcome. RESULTS: Among 390 analyzed patients (median age, 57 years; 187 [48%] women), median (IQR) hospital length of stay was 6 (3–10) days. Administration of aspirin, compared with placebo, did not significantly reduce the incidence of ARDS at 7 days (OR, 1.24; 92.6%CI, 0.67–2.31). No significant differences were seen in secondary outcomes or adverse events. [Table: see text] CONCLUSIONS AND RELEVANCE: Among at-risk patients presenting to the ED, the use of aspirin compared with placebo did not reduce the risk of ARDS at 7 days. The findings of this phase 2b trial do not support continuation to a larger phase 3 trial.